PEMETAAN INDIKATOR SUSTAINABLE DEVELOPMENT GOALS (SDGs) YANG BERPOTENSI SEBAGAI INDIKATOR RENCANA PEMBANGUNAN JANGKA MENENGAN KABUPATEN INDRAGIRI HILIR 2019 - 2023 - Roberta Zulfi Surya (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
SDGs consist of 17 goals, 169 targets and 241 indicators in social dimension coverage, economic and environment, law and good governance. The study has been done by desk review method; which is collecting data technique and information through checking and data analyzing. The document that can be used as the object of study is the indicators of SDGs Action Plan of Indragiri Hilir District 2013 - 2018 (Pilot Project UNDP), the documents of SDGs Action Plan of Riau Province, SDGs Action Plan of Indonesian Republic and Meta Data SDGs. In order to develop the mapping result, then do a discussion about aspect by stakeholder. Based on the mapping result through the goals, targets and indicators of SDGs; the potential one of indicators of Sub-national Mid-Term Development Planning (RPJMD) of Indragiri Hilir District 2018 - 2023 is about 15 goals, 68 targets and 153 indicators.